Orbital Selectivity in Electron Correlations and Superconducting Pairing of Iron-Based Superconductors - Yu, Rong; Hu, Haoyu; Nica, Emilian M.; Zhu, Jian-Xin; Si, Qimiao (Frontiers in Physics, 2021)
Electron correlations play a central role in iron-based superconductors. In these systems, multiple Fe 3d-orbitals are active in the low-energy physics, and they are not all degenerate. For these reasons, the role of orbital-selective correlations has been an active topic in the study of the iron-based systems. In this paper, we survey the recent developments on the subject. For the normal state, we emphasize the orbital-selective Mott physics that has been extensively studied, especially in the iron chalcogenides, in the case of electron filling n 6. In addition, the interplay between orbital selectivity and electronic nematicity is addressed. For the superconducting state, we summarize the initial ideas for orbital-selective pairing, and discuss the recent explosive activities along this direction. We close with some perspectives on several emerging topics. These include the evolution of the orbital-selective correlations, magnetic and nematic orders and superconductivity as the electron filling factor is reduced from 6 to 5, as well as the interplay between electron correlations and topological bandstructure in iron-based superconductors.